Artroplastia total híbrida nacional em cães Portadores de displasia coxofemoral - Rossetto, Victor José Vieira [UNESP] (2015)
Total hip arthroplasty is generally the most commonly performed surgical technique for severe hip dysplasia treatment in humans and dogs, and consists of the replacement of the hip joint by prosthetic components. The aim of this study was to evaluate the hybrid total arthroplasty, developed in Brazil, as a treatment option for dogs with moderate or severe hip dysplasia up to 180 days after surgery by clinical, radiographical and tomographical evaluations, and the frequency of the potential complications. For this, we utilized 10 dogs of variable breeds, skeletally mature, male and female, with moderate or severe hip dysplasia and submitted to total hip arthroplasty using cemented femoral component of exchangeable head and cementless acetabular component. The dogs were evaluated by orthopaedic and radiographical examinations at imediate postoperative period, and at 30, 60, 120 and 180 days after surgery; and by CT scan at imediate postoperative period, and at 120 and 180 days after surgery. Surgery conferred improvement of the locomotor function and intensity of pain in, respectively, 60% and 90% of the evaluated animals. Among the selected animals, six (60%) had postoperative complications. Major complications included infection, aseptic loosening of the femoral component, femoral component dislocation and femoral periprosthetic fracture. The selection of owners and animals must be rigorous in trying to greatly reduce the complications observed